ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANI RUMPUT LAUT DESA TOYAPAKEH NUSA PENIDA KABUPATEN KLUNGKUNG - Junior, Medy Prasetya; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Welfare is one of the development goals expected by each region, including the regencies / cities of Bali Province. Welfare can be achieved if decent work opportunities are created and are able to provide income that can guarantee the lives of workers and families. The purpose of this study was to determine the effect of capital, labor, land area, and production on business income directly or through the amount of seaweed farmer production in Toya Pakeh Village, Nusa Penida District. The data used are primary data, using Saturated Sampling. The sample in this study amounted to 40 samples. The analysis technique used is the path analysis technique (path analysis). The results showed that (1) Capital, labor, land area had a positive effect on the production of seaweed farmers in Toya Pakeh Village, Nusa Penida District, (2) Capital, labor, land area, and production had a positive effect on the opinion of seaweed farmers in Toya Pakeh Village, Nusa Penida District (3) Capital, labor, land area, has a negative effect on business income through the production of seaweed farmers in Toya Pakeh Village, Nusa Penida District.   Keywords: Capital, Labor, Land area, Production, Farmer Income.